2016
DOI: 10.5527/wjn.v5.i1.20
|View full text |Cite
|
Sign up to set email alerts
|

How do kinases contribute to tonicity-dependent regulation of the transcription factor NFAT5?

Abstract: NFAT5 plays a critical role in maintaining the renal functions. Its dis-regulation in the kidney leads to or is associated with certain renal diseases or disorders, most notably the urinary concentration defect. Hypertonicity, which the kidney medulla is normally exposed to, activates NFAT5 through phosphorylation of a signaling molecule or NFAT5 itself. Hypotonicity inhibits NFAT5 through a similar mechanism. More than a dozen of protein and lipid kinases have been identified to contribute to tonicity-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 140 publications
(225 reference statements)
0
23
0
Order By: Relevance
“…CDK5, c-Abl, and ATM promote the nuclear localization of NFAT5, and, in contrast, CK1 inhibits its nuclear accumulation [19]. There are many other factors that influence the activation and expression of NFAT5, such as inflammatory cytokines [16, 77], microRNAs [50, 62, 78, 79], and transcription factors [80-83].…”
Section: The Regulation Of Nfat5 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK5, c-Abl, and ATM promote the nuclear localization of NFAT5, and, in contrast, CK1 inhibits its nuclear accumulation [19]. There are many other factors that influence the activation and expression of NFAT5, such as inflammatory cytokines [16, 77], microRNAs [50, 62, 78, 79], and transcription factors [80-83].…”
Section: The Regulation Of Nfat5 Activationmentioning
confidence: 99%
“…Like many other biological processes, activation of NFAT5 is determined by its phosphorylation sites. Hypertonicity and hypoxia promptly increased the phosphorylation of NFAT5, and it could be phosphorylated at many sites [17-19]. Furthermore, the phosphorylation and nuclear location of NFAT5 were regulated by several kinases, such as p38 [20], ATM [21], GSK-3β [22], CDK5 [23], and CK1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…NFAT5 expression is known to be upregulated by hypertonicity (1, 2) and dehydration (13). Accordingly, increase in osmolarity by the addition of 40 mM NaCl to culture medium of MEG‐01 cells and water deprivation of mice increased NFAT5 expression, an effect paralleled by increase of Orai1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor of activated T cells 5 (NFATS) or tonicity responsive enhancer (TonE) binding protein (TonEBP), was originally cloned as a cell volume–regulated transcription factor upregulated by osmotic cell shrinkage (1, 2). NFAT5‐sensitive genes include serum and glucocorticoid‐inducible kinase 1 (SGK1) (3), which in turn leads to phosphorylation and thus degradation of the inhibitor protein IkBα resulting in nuclear translocation of the transcription factor NFkB (4).…”
mentioning
confidence: 99%
“…Furthermore, how changes in tonicity are converted into functional outputs via NFAT5 remains elusive. More than a dozen protein kinases have been identified that contribute to tonicity-dependent regulation of NFAT5 [3]. Hypertonicity activates NFAT5 by increasing its nuclear localization and by transactivating its activity in the early phase and protein abundance in the late phase of activation.…”
mentioning
confidence: 99%